2012
DOI: 10.1111/j.1469-8129.2011.00534.x
|View full text |Cite
|
Sign up to set email alerts
|

The tyranny of transnational discourse: ‘authenticity’ and Irish diasporic identity in Ireland and England

Abstract: Through the prism of current state discourses in Ireland on engagement with the Irish diaspora, this article examines the empirical merit of the related concepts of ‘diaspora’ and ‘transnationalism’. Drawing on recent research on how Irish identity is articulated and negotiated by Irish people in England, this study suggests a worked distinction between the concepts of ‘diaspora’ and ‘transnationalism’. Two separate discourses of authenticity are compared and contrasted: they rest on a conceptualisation of Iri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…But, because of this, diaspora governmentalities are also fragile and contingent, and can be easily dismantled or destroyed (Gamlen, 2013). Often, this is because of a failure to make convergences with a diversity of experiences and agendas, as Scully's (2011) study of the Irish state's contested discourses of Irish authenticity showed. It may also be because diaspora organising around the complex socio-geographical intersectionalities of diasporic subjectivities through, for instance, hometown associations, offers more legitimate alternatives (Moya, 2005;Mercer et al, 2008).…”
Section: Diaspora and Governmentalitymentioning
confidence: 94%
See 1 more Smart Citation
“…But, because of this, diaspora governmentalities are also fragile and contingent, and can be easily dismantled or destroyed (Gamlen, 2013). Often, this is because of a failure to make convergences with a diversity of experiences and agendas, as Scully's (2011) study of the Irish state's contested discourses of Irish authenticity showed. It may also be because diaspora organising around the complex socio-geographical intersectionalities of diasporic subjectivities through, for instance, hometown associations, offers more legitimate alternatives (Moya, 2005;Mercer et al, 2008).…”
Section: Diaspora and Governmentalitymentioning
confidence: 94%
“…Nonetheless, there is also a need to account for the local contexts in which diaspora policies are implemented, received and translated by diasporic populations embedded in 'host' countries so as to better understand specific policies' successes and failures (Délano, 2011). The messy actualities of overseas populations' diasporic identifications, which may not always be coherently aligned to an 'origin' country, means that diaspora outeach practices may not always find resonances (McCann, 2010;Scully, 2011). If, as Mullings (2011: 424) agues, a key aim of scholarly investigation should be to analyze how diaspora policy formations ''seek out, and recognize as legitimate .…”
Section: Introductionmentioning
confidence: 96%
“…Material transnationalism concerns various circuits through which either money or various kinds of merchandise cross national borders (Levitt 2001;Scully 2012). Here, it is mostly about the transfer of costumes between Croatia and dance groups in Australia.…”
Section: Materials Exchangesmentioning
confidence: 99%
“…She claims he actively encourages stereotypical activities, such as Irish sports, music and awareness of Irishness. Scully (2012) noted that these proactive displays of Irishness were perceived as ‘old fashioned’ and inauthentic by Irish ‘new arrivals’ and second-generation Irish in England, whereas Áine treats her husband’s proactive transmission as him having a stake in their children being Irish, and described his behaviour as accountable – ‘he’d be pushing’ (extract 5, line 5). Áine’s account of this excessive transmission by her husband indirectly positions her as being more reasonable through the relative passivity of her transmission style.…”
Section: Data and Analysismentioning
confidence: 99%